Penguatan Pendidikan Agama Hindu Pada Upacara Ngusaba Desa Di Desa Kutuh, Kabupaten Badung - Sri Ekawati, Ni Kadek; Uma Lestari, Ni Putu Prawani; Saputra, I Gede Andre (Metta : Jurnal Ilmu Multidisiplin, 2023)
The ngusaba desa ceremony held in Kutuh Village is one of the ancestral legacies from ancient times, which is held once a year at panglong apisan (1) sasih kapat. The ngusaba desa ceremony was held at Puseh Temple and Toyaning Temple as a form of community gratitude for Ida Sang Hyang Widhi Wasa, who manifested as Lord Vishnu in the form of the fertility of the Kutuh Village community's plantations. The purpose of this study was to describe the strengthening of Hindu religious education at the Nusaba Desa ceremony in Kutuh Village, Badung Regency. The method used is qualitative by collecting data using observation techniques, interviews, and literature study. The collected data were analyzed using a qualitative descriptive analysis technique following data reduction, data presentation, verification, and conclusion. The results showed that: 1) The form of strengthening Hindu religious education at the ngusaba desa ceremony was divided into several stages, namely: strengthening sraddha bhakti, strengthening the principle of menyamabraya, strengthening the focus of environmental awareness, and strengthening universal religious values. 2) Obstacles were faced and efforts made at the ngusaba desa ceremony: obstacles in strengthening Hindu Religious education, obstacles in processions, and constraints in inheriting the value of Hindu Religious education. 3) There are Implications in strengthening Hindu religious education at the ngusaba desa ceremony in Kutuh Village: theological, social, and educational implications.